A High‐Performance Application Specific Integrated Circuit for Electrical and Neurochemical Traumatic Brain Injury Monitoring. Issue 10 (9th March 2018) - Pagkalos, Ilias; Rogers, Michelle L.; Boutelle, Martyn G.; Drakakis, Emmanuel M.
Abstract: This paper presents the first application specific integrated chip (ASIC) for the monitoring of patients who have suffered a Traumatic Brain Injury (TBI). By monitoring the neurophysiological (ECoG) and neurochemical (glucose, lactate and potassium) signals of the injured human brain tissue, it is possible to detect spreading depolarisations, which have been shown to be associated with poor TBI patient outcome. This paper describes the testing of a new 7.5 mm 2 ASIC fabricated in the commercially available AMS 0.35 μm CMOS technology. The ASIC has been designed to meet the demands of processing the injured brain tissue's ECoG signals, recorded by means of depth or brain surface electrodes, and neurochemical signals, recorded using microdialysis coupled to microfluidics‐based electrochemical biosensors. The potentiostats use switchedcapacitor charge integration to record currents with 100 fA resolution, and allow automatic gain changing to track the falling sensitivity of a biosensor. This work supports the idea of a "behind the ear" wireless microplatform modality, which could enable the monitoring of currently non‐monitored mobile TBI patients for the onset of secondary brain injury. Abstract : A new chip for the monitoring of patients who have suffered a traumatic brain injury (TBI) is presented. By monitoring the neurophysiological and neurochemical signals of the injured human brain tissue, it is possible to detect spreading depolarisations associated with poor TBI patient outcome. This work supports the idea of a "behind the ear" wireless microplatform modality, which could enable the monitoring of mobile TBI patients for the onset of secondary brain injury.